STUDI KEBIJAKAN PENANAMAN MODAL INDONESIA - May Hermawan (DIA: Jurnal Administrasi Publik, 2019)
Investment is one form of economic politics carried out in the context of economic democracy. As stated in the Ketetapan Majelis Permusyawaratan Rakyat Republik Indonesia Nomor XVI/MPR/1998 concerning Economic Politics in the framework of Economic Democracy, investment policies always underlie people's economy which involves the development of micro, small, medium and cooperative businesses. Investors who aim to exploit the resources and means of production at low prices are interesting to put forward if viewed from what issues and how investment policies in Indonesia maintain national economic activity? This policy study uses the library research method.